Legume pasture units for supplementing cattle grazing rangeland under traditional production systems in the Nigerian subhumid zone - Kaufmann, Ralph R. von; Mohamed-Saleem, M.A. (French Grassland Society, 1989)
Results of a study conducted to determine the productivity, composition & quality of fodder banks under different management systems and the milk and liveweight output with and without fodder banks on legume pasture units established for supplementing cattle grazing rangeland under traditional production systems in the Nigerian subhumid zone.